TAWAKAL ATTITUDE AND GRATITUDE AS A STEP TO RELIEVE BIPOLAR DISORDER - Abdulkarim Duerawee; Asiyah Kuwing (Universitas Pendidikan Indonesia, 2022)
Sudden or sudden changes in mood or feelings are normal for some people, but not for people with bipolar disorder. People with bipolar disorder experience significant mood changes that can hurt themselves, and others around them as a result of the mental stress they suffer. Islam as a religion of Rahmatan lil Alamin provides a solution, by inviting and ordering people to be tawakal and grateful. In writing scientific journal articles, the method of writing articles based on literature review. The research method used is a qualitative method that focuses on library research or library research. As Muslims we are obliged to instill a tawakal attitude and be grateful for the will of Allah SWT. Bipolar disorder is basically a mental disorder whose cause is a lack of gratitude. With an attitude of tawakal and our efforts, we can increase our inner gratitude, and foster a better belief in Allah SWT, so as to relieve bipolar disorder. People with bipolar disorder or other mental illness disorders should draw closer to Allah SWT. Hopefully we as Muslims can always get closer to Allah SWT., Think positively, and behave properly and properly in order to avoid various diseases, especially mental illness